Aulas de Matemática: resolução de problema no 1º ano do Ensino Fundamental - Gualdi, Ana Paula Hanke da Silveira (2015)
The construction of mathematical knowledge occurs in the daily experiences of student, at times when it uses personal strategies to solve its problems. Mathematics is present in its lives from birth and they are in contact with it at all times. However, for the student to have initiative to solve challenges, in addition to its interest, it s necessary interest from the teacher, who should assume the role in encouraging and guiding this process of knowledge construction, which the students should be the center of learning. Given the gaps in teacher's initial education to teach mathematics and believing in the importance of using the problem solving in the student learning process, the focus of this research is Teaching of Mathematics through problem solving, with the central question in this research: how to use problem solving in first grade of the elementary school, promoting teacher development and improving the educational practices in math classes? The research aims to analyze teacher s conceptions of the use of problem solving in first grade of the elementary school, and based on this information, to develop a training proposal, using problem solving as a teaching methodology. In addition, the specific objectives of the research are: conduct a theoretical survey of authors who work in the area of problem solving; identify and analyze the national and state legal texts that describe the elementary school and the teaching of mathematics in the early years; and set priorities with regard to work with problem solving in first grade of elementary school, based on consultation with teachers. The research was conducted as a qualitative research and it used as data collection instrument the bibliographical and documentary research, besides the application of questionnaires to teachers who work in first grade of elementary public school, which belongs to Diretoria Leste 1 in the city of São Paulo. The questionnaire was used to know the understanding of these teachers, in relation to work in mathematics and problem solving. Based on the analysis of their responses, it was proposed a continuing education program in order to organize the conditions to qualify school education in first grade, with an emphasis on mathematics. Continuing education should occur in one semester, using the moments of collective work in the school for the discussion of mathematics and the use of problem solving as a teaching methodology in the classroom, providing study opportunities, discussion, preparation, implementation, and analysis of the resolutions